The Experiences of African American Female Students as a Result of Exclusionary School Suspensions - Jones, Karen (My University, 2022)
I investigated six African American female students’ perceptions of exclusionary discipline and its impact on their education. I examined how their childhood and school years shaped their roles as high school students. This study contributes to the limited academic literature on African American female students, focusing on the intersection of their race and gender obstacles they overcame to find success as high school graduates. It also uses women’s voices in rural South Georgia to tell their own stories. To understand the young women’s main characteristics of receiving exclusionary discipline and affecting their risk of dropping out of high school, I used two theoretical frameworks: Critical Race Theory and Black Feminist Thought. I developed three analytical themes from the data: 1) strained relationships, 2) power of one, and 3) fighting to survive. The findings suggest that African American female students felt targeted and unheard in school. Many participants made choices based on their home and community experiences. The findings also suggest that African American female students adapted their behaviors to survive in a White middle-class school system. The participants illustrated resilience and persistence to graduate. The social, political, and economic challenges African American female students face in their day-to-day lives influenced their school behavior and academic performance. The findings from this study are significant for educators, parents, students, teacher preparation programs, and lawmakers because the exclusionary discipline of African American female students needs to be addressed in an effort to reduce the number of suspensions.
Keywords: African American high school students; African American women; African Americans--Education; Critical race theory; Dissertations, Academic--United States; Education; Educational leadership; Student suspension